2009
DOI: 10.1161/strokeaha.109.550053
|View full text |Cite|
|
Sign up to set email alerts
|

Brain Activity Changes Associated With Treadmill Training After Stroke

Abstract: Background and Purpose-The mechanisms underlying motor recovery after stroke are not fully understood. Several studies used functional MRI longitudinally to relate brain activity changes with performance gains of the upper limb after therapy, but research into training-induced recovery of lower limb function has been relatively neglected thus far. Methods-We investigated functional reorganization after 4 weeks of treadmill training with partial body weight support in 18 chronic patients (mean age, 59.9Ϯ13.5 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
108
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(117 citation statements)
references
References 44 publications
6
108
1
2
Order By: Relevance
“…A number of previous studies have investigated the role of exercise in promoting enhanced cell survival against brain ischemia and improved functional recovery [30,31]. Our result show that physical training significantly promoted the functional outcomes on day 14 after MCAO.…”
Section: Discussionsupporting
confidence: 50%
“…A number of previous studies have investigated the role of exercise in promoting enhanced cell survival against brain ischemia and improved functional recovery [30,31]. Our result show that physical training significantly promoted the functional outcomes on day 14 after MCAO.…”
Section: Discussionsupporting
confidence: 50%
“…Additionally, 1 RCT demonstrated that progressive treadmill walking improves cardiovascular fitness, economy of gait, and endurance (ie, 6-minute walk test) compared with stretching and low-intensity walking. 32 Recently, brain activity changes were observed with functional magnetic resonance imaging after treadmill training, 223,224 which suggests that cortical reorganization is possible during task-specific LE activity.…”
Section: Activities and Participationmentioning
confidence: 99%
“…32,33 Increased brain activity within this region during active ankle movements has been linked to better walking performance in stroke subjects. 34 The cerebellum is critical for intralimb and interlimb coordination of cyclic movements, along with the dynamic regulation of balance. 35,36 Atrophy of this region has been linked to poor walking outcomes in community-dwelling older adults.…”
mentioning
confidence: 99%